Alat Atau Media Pembelajaran - Sriyono Fauzi; Warih Nurul Hidayati; Sholekhah Nur Afifah; Nur Ali Rahmatullah (Journal of Student Research, 2024)
For the realization of the educational goals of Islamic education, it is necessary to consider that everything supports the success of the educational program. Because success in the learning process is one of the most important factors. For this reason, it is necessary to create a conducive atmosphere in the learning process, so that students are really interested and actively participate in the learning process.In relation to efforts to create a conducive atmosphere, the media and educational tools can Because media and educational tools are means that help the learning process, especially those related to the sense of hearing and vision. With the availability of teaching tools and media, teachers can create various classroom situations, determine teaching methods to be used in different situations and create a healthy emotional climate among their students. In fact, this teaching tool/media further helps teachers bring world into the classroom.